2020
DOI: 10.1002/ptr.6667
|View full text |Cite
|
Sign up to set email alerts
|

The influence of green coffee bean extract supplementation on blood glucose levels: A systematic review and dose–response meta‐analysis of randomized controlled trials

Abstract: Studies regarding the influence of green coffee extract (GCE) on blood glucose levels are conflicting. Thus, we sought to conduct a meta‐analysis and systematic review of all available randomized controlled trials (RCTs) to quantify the effects of GCE and CGA intervention on blood glucose and insulin levels. We performed systematic online searches in Scopus, Web of science, and PubMed databases, from inception to July 2019. Data were combined analyzed using a random effects model (Der Simonian‐Laird method) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
(92 reference statements)
2
3
0
Order By: Relevance
“…The digestive enzyme binding with GCBE is inactivated, reducing blood sugar levels. Therefore, the present results indicate that GCBE is a potential compound to act against hyperglycemia, consistent with results reported in previous studies in vitro, in vivo, and in clinical trials [13,35,37] Macrophages are usually used as a model to study the anti-inflammatory effect of drugs or plant extract because they are the principal immune cells responsible for inflammation of various organs. Macrophages produce cytokines and reactive oxygen species (ROS), producing oxidative stress and increased activation of the inflammation pathway [38].…”
Section: Discussionsupporting
confidence: 92%
“…The digestive enzyme binding with GCBE is inactivated, reducing blood sugar levels. Therefore, the present results indicate that GCBE is a potential compound to act against hyperglycemia, consistent with results reported in previous studies in vitro, in vivo, and in clinical trials [13,35,37] Macrophages are usually used as a model to study the anti-inflammatory effect of drugs or plant extract because they are the principal immune cells responsible for inflammation of various organs. Macrophages produce cytokines and reactive oxygen species (ROS), producing oxidative stress and increased activation of the inflammation pathway [38].…”
Section: Discussionsupporting
confidence: 92%
“…Also, the results of the present study are consistent with two meta-analyses and a review [50][51][52] that reported that green coffee extract has no significant effect on insulin and HOMA-IR levels.…”
Section: Paper Food and Functionsupporting
confidence: 92%
“…We found that while EX caused weight loss in the PD mice, GC and CGA alone had no effect, as we found, others reported that EX promoted weight loss and improvement in body composition. However, there effects of GC and CGA on weight loss are controversial [ 17 , 20 , 31 33 ]. It is possible that variation in study design and dosages explain variation in reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Green coffee (GC) is unroasted, increasing in use, is thought to have antioxidant and antiinflammatory properties, and has been propped as a treatment for certain diseases. Green coffee is rich in phytochemicals such as chlorogenic acid (CA) that is believed to be the main source of its beneficial properties [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%